Hyperenteroglucagonaemia and small intestinal mucosal growth after colonic perfusion of glucose in rats. Issue 5 (May 1985) - Miazza, B M; Al-Mukhtar, M Y; Salmeron, M; Ghatei, M A; Felce-Dachez, M; Filali, A; Villet, R; Wright, N A; Bloom, S R; Crambaud, J C
Abstract : Beside intraluminal factors, humoral agents play an important role in intestinal adaptation. Enteroglucagon, the mucosal concentration of which is maximal in the terminal ileum and colon, is the strongest candidate for the role of small intestinal mucosal growth factor. The present experiment was designed to study the role of colonic enteroglucagon in stimulating mucosal growth in rats with a normal small intestine. After eight days of glucose large bowel perfusion, enteroglucagon plasma concentrations were 120.7 +/- SEM 9.2 pmol/l, versus 60.1 +/- 6.8 in mannitol perfused control rats (p less than 0.001). Gastrin, cholecystokinin, neurotensin, pancreatic glucagon, and insulin plasma concentrations were unchanged. Crypt cell proliferation, measured by the vincristine metaphase arrest technique, increased significantly in the small intestine of glucose perfused animals (p less than 0.005-0.001) in comparison with the controls. This resulted in a greater mucosal mass in both proximal and distal small bowel: mucosal wet weight, DNA, protein and alpha D-glucosidase per unit length intestine were all significantly higher (p less than 0.05-0.001) than in mannitol perfused rats. Our data, therefore, support the hypothesis that enteroglucagon is an enterotrophic factor and stress the possible role of the colon in the regulation of small bowel trophicity.